Understanding national IR disciplines outside the United States: political culture and the construction of International Relations in Denmark - Breitenbauch, Henrik Ø; Wivel, Anders (Journal of international relations and development, 2004)
The conventional view of the discipline of international relations (IR) as an ‘American social science’ leaves little room for national traditions of international relations theorizing. We challenge this view by constructing and applying a theoretical model conceptualizing the relationship between societal and scientific developments and the construction of national IR disciplines. Taking our point of departure in this model, we map the gradual development of the study of international relations as an academic discipline in Denmark and explain how the form and content of the Danish discipline continue to reflect important traits of that country's political culture. We argue that the effect of political culture is subject to structural constraints set by geopolitics, market size and global theoretical trends. In accordance with this view, the American influence on the discipline is seen as a structural constraint defining the boundaries of the discipline and serving as a major source of global theoretical trends.